Numerical Modeling of the Gob Loading Mechanism in Longwall Coal Mines - Khaled Morsy (International Conference on Ground Control in Mining, 2002)
Longwall mining is one of the most widely practiced underground coal mining method. The behavior of the longwall gob is very critical in the understanding of the complex ground response to longwall mining. In the limited data available, the values of gob moduli used in numerical modeling ranged from 1,000 psi to over 300,000 psi. Such a wide variation in moduli would greatly affect the results of the numerical analysis. A better understanding of the behavior of the gob will allow numerical models to be more accurate for simulating longwall mining conditions. In this study, a gob model based on the Terzaghi's model was incorporated into the comprehensive finite element package, ABAQUS, to simulate the loading behavior of longwali gob material. A case study was used to verify the proposed gob model.